The Light at Wyndcliff - Ladd, Sarah E. (Nashville, Tennessee : Thomas Nelson, 2020)
"In the third book of this ... Regency Cornwall series, one young man must search for truth among the debris of multiple shipwrecks on his newly inherited property"--
Keywords: Shipwrecks -- Fiction; Manors -- Fiction -- 19th century -- England; Man-woman relationships -- Fiction; Cornwall (England : County) -- Fiction -- History -- 19th century; Regency fiction; Historical fiction; Religious fiction; Romance fiction